Organisation et dynamiques de l’occupation du sol au nord-ouest de Cenabum-Orléans (Loiret) du ier s. av. n. è. au ve s. de n. è. - Laure de Souris (Revue Archéologique du Centre de la France)
This work deals with the organization of the countryside to the northwest of the agglomeration of Orléans (Loiret) during the Roman period, from 1st century BC to the 5th century AD It is based on data from documentation about rural settlements surveyed, diagnosed or excavated. The area studied includes the northwest quarter of the territory of the commune of Orléans and seven other contiguous communes: Cercottes, Fleury-les-Aubrais, Gidy, Ingré, Ormes, Saint-Jean-de-la-Ruelle, Saran.Criteria for prioritizing these sites were established using archaeological and environmental descriptors. A classification of 43 sites was obtained using multiple correspondence analysis (MCA). Despite its dependence on the quality of information available upstream, it defines five classes of housing, ranging from the villa to more modest settlements.These results were compared with the distribution of settlement and its density. The structure of the sowing of points, highlighted using exploratory spatial analyses, shows grouped sites, the distances of the groupings having however not been able to be defined. Would a larger corpus and a wider study window have made it possible to overcome the pitfalls undoubtedly due to too few sites and, thus, to push the interpretations further here?